The Efficacy of Mineral-Amino Acid Complex (Zn, Mn, Cu, Fe and Se) on White Shrimp, Litopenaeus vannamei, Diets - Jintasataporn, Orapint; Ward, Terry; Chumkam, Srinoy; Jintasataporn, Oratai (Indonesian Aquaculture Society (MAI), 2015)
The efficacy of mineral-amino acid complex of Zn,Mn,Cu,Fe and Se for white shrimp, Litopenaeus vannamei, diet compare to inorganic mineral on growth performance, feed utilization and immunity was studied. The treatments were 1) the control diet with contained inorganic minerals of Zn, Mn, Cu, Fe and Se (T1-C1X). 2) treatment diet of the combination of inorganic mineral and organic mineral-amino acid complex70:30 at the same level of control diet Availa Zn, Availa Cu, AvailaMn, Availa-Fe 100and Availa-Se 1000 (T2- Inorg:org 1X) and 3) The sole mineral-amino acid complex Availa Zn, Availa Cu, AvailaMn, Availa-Fe 100 and Availa-Se 10000 at 0.5X (T3-Org 0.5X). The results indicated that there were not significantly different (P>0.05) on the growth performance, feed consumption, feed conversion ratio, Protein efficiency ratio and survival rate. The immune status in term of hemocyte count were significantly increase (P<0.05) in group of shrimp fed mineral-amino acid complex than control. Drip loss of peel shrimp on 96 hr was low (P<0.05) in group of shrimp fed mineral-amino acid complex than control. Therefore, mineral-amino acid complex of Zn, Mn, Cu,Fe and Se at 0.5X (T3-Org0.5X) exhibited the same growth performance, feed utilization and survival rate as inorganic mineral (T1-C1X) and combination of inorganic and organic mineral-amino acid complex (T2- Inorg:org 1X). Hence, organic mineral-amino acid complex has the efficacy around 200% of inorganic mineral on shrimp growth performance. Keywords : mineral-amino acid complex ( AvailaZn,Mn,Cu,Fe and AvailaSe); white shrimp; growth performance; immunity; drip loss